2006
DOI: 10.1007/s10549-006-9274-0
|View full text |Cite
|
Sign up to set email alerts
|

Early arm swelling after breast surgery: changes on both sides

Abstract: These findings demonstrate that limb segment volume changes affect a greater proportion of patients during the first 6 weeks following surgery than previously recorded. They also indicate that flow of lymph from the side of surgery to the contralateral side may disperse lymph between sides during this early post-operative period. This has implications for how swelling is measured during this period and strategies to prevent onset of lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…It is interesting to note that the changes were evident predominantly on the unaffected upper limb and in the proximal limb segments. Previous investigations have identified that both affected and unaffected sides increase in volume in the early stages post-surgery and that this is most prominent in proximal upper limb segments [12]. It is unknown whether early changes in upper limb volumes are related to later development of more severe lymphedema symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the changes were evident predominantly on the unaffected upper limb and in the proximal limb segments. Previous investigations have identified that both affected and unaffected sides increase in volume in the early stages post-surgery and that this is most prominent in proximal upper limb segments [12]. It is unknown whether early changes in upper limb volumes are related to later development of more severe lymphedema symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The EORTC C30 (version 3.0) instrument [10] with BR23 supplement was also used to measure elements of disease-specific health-related quality of life that might explain changes in generic health-related quality of life [11]. Secondary outcome measures included upper limb swelling (circumferential measurements of the upper limb taken at the level of the metacarpal-phalangeal joint, ulnar styloid, then 10, 20, 30 and 40 cm proximally along the upper limb from the ulnar styloid) [12], body composition (muscle mass %, body fat %-measured using foot-to-foot bioelectrical impedance analysis) [13], cancer-related fatigue (Multidimensional Fatigue Index) [14], general physical capacity (Balance-Functional Reach [15], Step Test [16], Strength-Grip, leg press and Endurance-6-min walk test [17]), and shoulder range of motion (flexion, abduction and external rotation-measured using plurimeter). Adverse events were documented prospectively by participants in a log book.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include: a 2 or 3 cm difference in one or more arm circumference measures; 7,8 a total difference in circumferential measurements of 5 cm or 5%; 9,10 an absolute inter-limb arm volume difference ranging from 125 to 200 mL, 7 or a 10%-20% inter-limb volume percentage change. 7,8,11,12 The most widely accepted measure of arm lymphedema is volume 13 and the most commonly used volume cut-off is a 200 mL volume difference. 7 The origins of these diagnostic thresholds are uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of patients in this study presented with an excess arm volume of less than 10%, a volume difference often considered to be mild or of no clinical significance [22][23][24]. A significant number of patients had no discernable arm volume difference between the affected and the contra-lateral arm, with 13% of patients presenting with less volume in the ipsilateral arm.…”
Section: Discussionmentioning
confidence: 96%